DIMENSI KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KPP PRATAMA SUKOHARJO - Esti Kurnia Sandy (Faculty of Economics and Business, Universitas Warmadewa, 2020)
Taxes are a source of state revenue that is used to build and improve infrastructure while enhancing the country's economy. In this study aims to examine the effect of service quality, religiosity of tax payments, tax amnesty policies, tax penalties, and the modern tax administration system on the compliance of individual taxpayers at KPP Pratama Sukoharjo. The population in this study is all private taxpayers who are registered in KPP Pratama Sukoharjo. The number of samples used in this research are 100 taxpayers registered in KPP Pratama Sukoharjo with Accidental Sampling techniques. Data collection using a questionnaire or questionnaire. The analysis method used by using multiple linear regression analysis. The results showed there was a positive influence between tax sanctions and the modern tax administration system on tax compliance for taxpayers at Sukoharjo KPP. Whereas service quality, religiosity of tax payments, and tax amnesty policies have a negative effect on taxpayers' compliance with Sukoharjo KPP. The benefit of this research is to improve information on taxation aspects, especially the increase in taxpayers in complying with taxation rules.